An in-depth investigation into the relationship between municipal solid waste generation and economic growth in the city of Cape Town - Van der Merwe, Carmen Louise (Stellenbosch : Stellenbosch University, 2020)
Thesis (MCom)--Stellenbosch University, 2020.